The contribution of nursing to health care seen through the „white heart“ symbol - Bošnjaković, Aleksandar (Education and Research in Health Sciences, 2023)
“The white heart“ as an international symbol of nursing care is a symbol that connects and unites all nurses in the world. Denoting care, tenderness, humanity, which are synonymous with the spirituality of nursing care, it represents the only vocation that seeks the most beautiful thing in a human being, and that is dedication to work and humanity in action. In the earliest periods of human society, the care for the sick was known, and drawings on the walls of caves have been preserved as witnesses, and it is mentioned in the oldest written historical documents. The beginnings of nursing are related to people of different professions, self-taught or partially qualified for the job, and health care existed only as a practice. Modern nursing care implies adequate education of staff and harmonization of education is widely present at the world level. It is the result of well-laid foundations for the development of nursing, and there is no doubt that it is the work of Florence Nightingale. Modern nursing practice is burdened with problems that can affect the quality of care provided, the safety of patients and the safety of nurses in the workplace. The health care system is the most complex system which, with its adequate functioning should provide physically, geographically and economically accessible, integrated and efficient health care. As a profession, nursing has developed through many developmental processes, always trying to adequately respond to the formulated problems of the profession, following the latest achievements and demands of community.
Keywords: nursing; health care; patient care